2012
DOI: 10.1371/journal.pone.0029957
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against the Envelope Glycoprotein Promote Infectivity of Immature Dengue Virus Serotype 2

Abstract: Cross-reactive dengue virus (DENV) antibodies directed against the envelope (E) and precursor membrane (prM) proteins are believed to contribute to the development of severe dengue disease by facilitating antibody-dependent enhancement of infection. We and others recently demonstrated that anti-prM antibodies render essentially non-infectious immature DENV infectious in Fcγ-receptor-expressing cells. Immature DENV particles are abundantly present in standard (st) virus preparations due to inefficient processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…This is evidenced by inefficient infectivity and high percentage of immature progeny virus in both mammalian and insect cells. Recently, it has been reported that during entry step, the pr-capped fusion loop of E protein could be cleaved by furin, allowing conformational change and fusion of E protein, which renders immature virus infectious (da Silva Voorham et al, 2012;Rodenhuis-Zybert et al, 2011). In the present study, our data provide supporting evidence that immature particles can also interact with claudin-1 protein on the cell surface, and might be capable to entry into the target cells via this interaction.…”
Section: Discussionsupporting
confidence: 84%
“…This is evidenced by inefficient infectivity and high percentage of immature progeny virus in both mammalian and insect cells. Recently, it has been reported that during entry step, the pr-capped fusion loop of E protein could be cleaved by furin, allowing conformational change and fusion of E protein, which renders immature virus infectious (da Silva Voorham et al, 2012;Rodenhuis-Zybert et al, 2011). In the present study, our data provide supporting evidence that immature particles can also interact with claudin-1 protein on the cell surface, and might be capable to entry into the target cells via this interaction.…”
Section: Discussionsupporting
confidence: 84%
“…High virus-neutralizing antibody titers (e.g., > 200) are generally associated with protection from viraemia, when measured using a plaque assay. 45,46 Despite our encouraging results, the increase in antibody levels (detected by ELISA) did not reflect the level of neutralizing activity. Interestingly, this observation may provide a clue to the availability of the epitopes that crosslink BCR with the CD21/ CD19/CD81 complex (the explanation of the adjuvanticity is in the constructions).…”
Section: Discussionmentioning
confidence: 65%
“…Immature or partially mature flavivirus particles of both DENV and WNV have been shown to account for up to as much as 40% of the total virus population in a given infection (135). While they were traditionally thought to be noninfectious, several recent studies have shown that immature WNV particles can be highly immunogenic and infectious in vitro and in vivo when bound by antibodies against the E or prM protein (43,51,179). These antibody-bound immature virus particles enter immune cells via the Fc receptor, resulting in productive infection.…”
Section: Life Cyclementioning
confidence: 99%